PENDAFTARAN TANAH DAN PENERBITAN SERTIPIKAT DALAM PERSPEKTIF FREE TRADE ZONE (FTZ) DI KAMPUNG TUA, KOTA BATAM, PROVINSI KEPULAUAN RIAU - Idham, Idham (Soumatera Law Review, 2019)
The implementation of land registration activities in Indonesia, namely by deriving on orders and mandates of Article 19 of the Basic Agrarian Law Number 5 of 1960 as intended, namely in accordance with developments and increasing demands for the acceleration and expansion of land registration activities in Indonesia and within the implementation of the land registration activities program in Indonesia still found several obstacles that were of a very conditional and structural nature and were greatly influenced by various factors of political development and the government system. This paper uses juridical empirical research methods, to support academic answers in this article. From the results of this journal writing, it turns out that the legal arrangements regarding land registration in the FTZ perspective in Kampung Tua, Batu Besar Village, Nongsa Sub-District, Batam City, have not been implemented properly, because some land rights in the area are still Management Rights controlled and registered. name of Batam Business Entity (BP Batam). Land registration has not been carried out based on existing positive law, as well as other inhibiting factors, namely due to the implementation of Regional Autonomy policies and FTZ policies in Batam City and the lack of budget political support.